An evaluation of a leadership development programme for women in STEMM in Antarctica. Issue 1 (2nd January 2018) - Nash, Meredith; Moore, Robyn
Abstract: In this paper, we explore the advantages and challenges of combining transformational tourism in Antarctica with a transformational leadership development programme for women. Our case study is a three-week leadership development course in Antarctica for women in STEMM that had the express purpose of increasing female leadership and visibility in the domain of climate change. Using a feminist sociological approach, we argue that synthesising transformational leadership development and transformational tourism in Antarctica has the potential to augment the effectiveness of both experiences and is particularly apt, given the programme's focus on climate change. Travelling to Antarctica as a group facilitated the development of strong bonds between the women, an important design feature of women's leadership development programmes. Additionally, exposure to the Antarctic landscape provided scope for awe-inspiring experiences that enhanced these relational bonds and led women to reflect on and/or challenge their views of themselves and their place in the world. We conclude that leadership development programmes for women in STEMM could be further strengthened by addressing gender essentialism. We also focus on issues associated with using Antarctica as a "stage" for climate protection – namely, the problematic depiction of women as "naturally" virtuous regarding environmental management.